Evaluasi Implementasi Program Sekolah Penggerak di SD Negeri Tamansari 03 Jakarta - Hidayatulloh, Hidayatulloh; Nuraini, Betti; Purwanto, Sigid Edy (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
The implementation of the Driving School Program at SD Negeri Tamansari 03 Jakarta faces challenges in implementing learning with a new paradigm, which causes this program to not run optimally. This is reflected in the low quality of schools in literacy and numeracy. This research aims to evaluate the implementation of the driving school program using the CIPP (Context, Input, Process, Product) method. This research involved school principals, teachers, students and parents using data collection techniques, namely interviews, observation and document study. The research results show that the driving school program which consists of five intervention activities, namely consultative and asymmetric assistance, strengthening school human resources, new paradigm learning, data-based planning, and school digitalization can improve the quality of learning, learning outcomes and student character. This is proven in the education quality report at SDN Tamansari 03 in 2024 which saw an increase in the literacy, numeracy and character aspects of students by 83.33%, while the learning quality aspect was 73.71%. So it can be concluded that the implementation of the driving school program contributes and has a positive impact on improving the quality of education at SDN Tamansari 03 Jakarta.